Pendampingan Revitalisasi Rumah Anak Bahari sebagai Pusat Literasi di Desa Merak Belantung - Yunita Mauliana; Yuli Purwanti; Sukarsih Sukarsih; Yayan Febriyanto; Ihwanudin Ma’ruf; Apriyanto Apriyanto; Nur Handoko (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Rumah Anak Bahari in Merak Belantung Village, Kalianda District, South Lampung Regency, is a reading facility initiated by the Indonesian Navy through the Pesisir Village Renovation II program in March 2016. However, the infrastructure at the Rumah Anak Bahari has deteriorated and the books has become inadequate. Beside that, children's interest in reading is increasingly eroded by gadgets and less useful digital content. Therefore, the purpose of this activity is to revitalize Rumah Anak Bahari by revitalizing the existing facilities and infrastructure so that Rumah Anak Bahari can be used as a literacy center, creating a comfortable educational space for children and adolescents, reducing dependence on gadgets, increasing knowledge, and instilling a love of literacy. This activity began with coordination with village officials and the management of Rumah Anak Bahari, followed by the implementation of revitalization activities, such as repairing signs, repainting the building, arranging the reading room, and making seating. Final stage was the handover of books as additional literature. This revitalization not only focuses on physical improvements and the provision of quality book, but also as a safe and educational space for children and adolescents in Merak Belantung Village.